Advancing the forecasting innovation pathways approach: hybrid and electric vehicles case. (2015) - Porter, Alan L.; Cunningham, Scott W.; Sanz, Alejandro
The forecasting innovation pathways (FIP) approach combines empirical tech mining with expert opinion. To date, FIP has been devised for relatively immature emerging technologies. This study extends the FIP methodology to work for a more advanced and complicated technology. It does so through a case analysis of hybrid and electric vehicles (HEVs). We retain the ten-step FIP process, augmenting several steps to deal with this more complex technology and technology delivery system (TDS). In particular, it is vital to address TDS sub-systems and attendant technical and market infrastructures. The key method to explore future prospects for the technology in question is an interactive workshop. Splitting into multiple workshop sub-groups proved constructive in addressing target markets and regional variations in innovation systems and policy options. The paper derives methodological suggestions to enrich FIP to address more complex technologies regarding scoping, sub-systems analyses, and ways to systematise key operations.